The meaning of caring for patients with cancer among traditional medicine practitioners in Uganda: A grounded theory approach. - John Baptist Asiimwe; Prakash B Nagendrappa; Esther C Atukunda; Grace Nambozi; Casim Umba Tolo; Patrick E Ogwang; Maud M Kamatenesi (Public Library of Science (PLoS), 2023)
Traditional medicine practitioners (TMPs) are a critical part of healthcare systems in many sub-Saharan African countries and play vital roles in caring for patients with cancer. Despite some progress in describing TMPs' caring experiences in abstract terms, literature about practice models in Africa remains limited. This study aimed to develop a substantive theory to clarify the care provided by TMPs to patients with cancer in Uganda. This study adhered to the principal features of the modified Straussian grounded theory design. Participants were 18 TMPs caring for patients with cancer from 10 districts in Uganda, selected by purposive and theoretical sampling methods. Researcher-administered in-depth interviews were conducted, along with three focus group discussions. Data were analyzed using constant comparative analysis. The core category that represented TMPs' meaning of caring for patients with cancer was "Restoring patients' hope in life through individualizing care." TMPs restored patients' hope through five main processes: 1) ensuring continuity in the predecessors' role; 2) having full knowledge of a patient's cancer disease; 3) restoring hope in life; 4) customizing or individualizing care, and 5) improving the patient's condition/health. Despite practice challenges, the substantive theory suggests that TMPs restore hope for patients with cancer in a culturally sensitive manner, which may partly explain why patients with cancer continue to seek their services. The findings of this study may guide research, education, and public health policy to advance traditional medicine in sub-Saharan Africa.